2017
DOI: 10.1039/c6nr07521e
|View full text |Cite
|
Sign up to set email alerts
|

A novel “tunnel-like” cyclopalladated arylimine catalyst immobilized on graphene oxide nano-sheet

Abstract: A novel "tunnel-like" cyclopalladated arylimine was prepared and immobilized on graphene oxide nano-sheet to form a hybrid catalytic material (denoted as F-GO-Pd) by self-assembly. The F-GO-Pd catalyst was characterized by XRD, FTIR, Raman, XPS, SEM, and TEM. This novel hybrid catalytic material was proven to be an efficient catalyst for the Suzuki-Miyaura coupling reaction of aryl halides (I, Br, Cl) with arylboronic acids in aqueous media under mild conditions with a very low amount of catalyst (0.01 mol%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 80 publications
1
50
0
Order By: Relevance
“…reported the synthesis of a novel “ tunnel‐like ” cyclopalladated arylimine grafted onto GO. The obtained material 149 was successfully applied as highly active catalyst for the Suzuki reaction between aryl halides and arylboronic acids (Scheme ) . Investigations on the catalytic process, involving kinetic studies, hot filtration, and poisoning tests, confirmed the heterogeneous nature of the catalytic system.…”
Section: Graphene‐ Graphene Oxide‐ and Reduced Graphene Oxide‐based mentioning
confidence: 88%
“…reported the synthesis of a novel “ tunnel‐like ” cyclopalladated arylimine grafted onto GO. The obtained material 149 was successfully applied as highly active catalyst for the Suzuki reaction between aryl halides and arylboronic acids (Scheme ) . Investigations on the catalytic process, involving kinetic studies, hot filtration, and poisoning tests, confirmed the heterogeneous nature of the catalytic system.…”
Section: Graphene‐ Graphene Oxide‐ and Reduced Graphene Oxide‐based mentioning
confidence: 88%
“…[25,26] The presence of a high density of carbonyl, hydroxyl and carboxylic acid groups on the biochar surface allows the modification of its surface via reaction with dopamine, alkoxysilane and other reagents which can be used as a support for the immobilization of catalysts or other substances. [33][34][35][36][37][38][39][40] The use of palladium-phosphine catalysts involves expensive, toxic and air-and moisture-sensitive procedures. Biochar is a stable solid in air atmosphere, at high temperature and in aqueous solution, and therefore biochar is an ideal catalyst support for organic processes occurring under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of immobilized palladium nanoparticles on graphene nanoplatelets (PdNPs-G) and reduced graphene oxide (PdNPs-rGO) as a catalyst was also evaluated in the model Suzuki-Miyaura coupling. As previously described, these supported catalysts, obtained from NanoInnova Technologies S.L., have shown good activity in the Suzuki cross-coupling of potassium aryltrifluoroborates with aryl halides [64]. However, under the studied conditions, these materials afforded 4-methoxybiphenyl (4) in a 30 and 40% conversion, respectively (Table 1, entries 10 and 11).…”
Section: Resultsmentioning
confidence: 74%
“…Very recently, we have shown that palladium nanoparticles (Pd NPs), supported on graphene and reduced graphene oxide, efficiently catalyze the Suzuki-Miyaura coupling between aryl bromides and potassium aryltrifluoroborates under aqueous and low loading conditions (0.1 mol % Pd) employing conventional or microwave heating [64]. Based on the experience and knowledge of our research group with oxime palladacycles as highly efficient precatalysts in cross-coupling reactions [65][66][67], herein we report a detailed study on the synthesis and characterization of new oxime palladacycle-graphene oxide non-covalent materials along with their catalytic activity in the Suzuki-Miyaura reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation